Improving food security through environmental management in lbadan: The case of the Ayeye community (2010)
Solid waste disposal is a nagging problem faced by various communities in Ibadan in southwest Nigeria and other state capitals. lbadan, the capital of Oyo State, is the most densely populated city in the state with over three million inhabitants. It is said that in Ibadan every street is a market. Many backyards are used for growing local vegetables and medicinal herbs.